PELATIHAN DIGITAL MARKETING MELALUI PEMBUATAN KONTEN DENGAN MEMANFAATKAN MEDIA DIGITAL SEBAGAI PENUNJANG PROMOSI WISATA DI DESA SUELA - Satrio Aprian, Dicky Rangga; Amni, Rauhatul; Khartiningsih, Indah Jelita; Muslim, Lalu Israhul; Janu, Aulia Syavira Dedare; Febrianti, Maelani Tazun Nisa; Safitri, Nia Holfiana; Labibah, Husna Muthia; Maulana, Habibi; Rinaldi, Lalu Surya Reza (Jurnal Wicara, 2025)
Digital media is currently used as a place for tourism promotion, increasing the popularity of a tourist attraction so that it becomes more well known to the public, therefore the aim of training in creating interesting content by utilizing digital media is a crucial thing carried out in Suela Village as a form of supporting sustainable ecotourism promotion. The method used in this activity is an educational persuasive approach using lecture, discussion and practice methods. In this case, socialization was chosen as a means of conveying information to the audience. The result of this activity is a video containing tourist content focused on digital media training material whose tourist attraction is Kembar Reservoir. More than 20 audiences attended, all of whom were youth and the Lemor Jaya Youth Organization, Suela Village. The conclusion of this training is that it can increase understanding regarding digital media and training on how to create content that attracts tourists to support sustainable ecotourism villages.